Y-Balance Test Performance Does Not Determine Non-Contact Lower Quadrant Injury in Collegiate American Football Players - Lace E Luedke; Turner W Geisthardt; Mitchell J Rauh (MDPI AG, 2020)
Collegiate American football has a high rate of injury. The Lower Quarter Y-Balance Test (YBT-LQ), a dynamic assessment of lower extremity strength, mobility, and balance, has been purported to identify athletes at risk for injury in different sports including football. Previous studies examining the association between YBT-LQ and injury have reported varied findings; therefore, the purpose of this study was to assess if preseason YBT-LQ performance predicted whether football players would sustain a non-contact lower extremity or low back (lower quarter (LQ)) injury during the season. Fifty-nine male collegiate American football players (age 20.8 ± 1.3 y, height 1.8 ± 0.1 m, body mass 94.6 ± 14.2 kg) completed a survey of training and injury history and had their YBT-LQ performance assessed at the start of the season. Athletic training staff tracked the occurrence of non-contact LQ injuries during the season. There were no significant relationships found between preseason YBT-LQ values and incidence of non-contact LQ injury in this population of collegiate American football players. This study is consistent with recent reports that have not found a significant association between preseason YBT-LQ values and LQ injury. These results suggest that, in isolation, the YBT-LQ may have limited utility as a screening test for non-contact injury in collegiate football players.